Association of previous cardiac surgery with outcomes in left ventricular assist device patients. (4th April 2020) - Ayers, Brian C; Wood, Katherine; McNitt, Scott; Goldenberg, Ilan; Chen, Leway; Alexis, Jeffrey; Vidula, Himabindu; Thomas, Sabu; Storozynsky, Eugene; Barrus, Bryan; Prasad, Sunil; Gosev, Igor
Abstract: OBJECTIVES: History of prior cardiac surgery has traditionally been considered a risk factor for subsequent cardiac procedures. The aim of this study was to investigate the outcomes of patients implanted with a left ventricular assist device via redo sternotomy. METHODS: Prospectively collected data were reviewed for all patients implanted with a continuous-flow left ventricular assist device at a single institution from December 2006 through June 2018. Patients were separated into 2 cohorts: those with a history of prior cardiac surgery (redo sternotomy) and those undergoing primary sternotomy at the time of left ventricular assist device implantation. The primary outcome was overall survival. RESULTS: Of the 321 patients included in the study, 77 (24%) were implanted via redo sternotomy and 244 (76%) via primary sternotomy. The redo sternotomy cohort was generally older (59 ± 10 vs 57 ± 12 years, P = 0.050) and had a higher incidence of ischaemic disease (70% vs 49%, P = 0.002). The Kaplan–Meier survival analysis demonstrated that overall survival was not significantly different between the redo sternotomy and primary sternotomy groups (6-month survival: 86% vs 92%; 5-year survival: 53% vs 51%; log-rank P = 0.590 for overall difference during follow-up). The propensity score analysis consistently showed that redo sternotomy was not significantly associated with mortality risk (hazard ratio 1.19, 95% confidence interval 0.73–1.93; P = 0.488). Redo sternotomy patients were more likely to require rehospitalization during their first year postoperatively ( P = 0.020) and spent less time out of the hospital during the first year ( P = 0.046). CONCLUSIONS: The redo sternotomy cohort represents a more technically challenging patient population, but overall survival similar to that of primary sternotomy patients can be achieved.